Enhancing Coronal Adaptation of Root Canal Fillings with a Modified Single-Cone Obturation Technique: Two Case Reports - Kalantar Motamedi, Mahmood Reza; Gillbert, Brett E.; Ha, William N (Iranian Endodontic Journal, 2024)
The single-cone technique, also known as the hydraulic condensation technique, is widely employed in endodontics. However, the aforementioned method is presented with certain limitations; specifically concerning the coronal seal and the adaptation of the coronal third of a master gutta-percha (GP) with a round cross-section to the coronal dentinal walls of root canals with semi-round or oval cross-sections. Through two case reports, the current article introduces the coronal vertical condensation (CVC) technique; aiming to enhance GP adaptation to canal walls in similar scenarios. In fact, the coronal vertical condensation technique amalgamates the different aspects of warm vertical condensation and single-cone techniques. In CVC, following the placement of the master GP cone, an electrical heat carrier is inserted immediately a few millimeters apical from the canal orifice to remove the coronal portion of the master GP cone. Subsequently, a hand plugger is used to condense GP in the vertical dimension, and the coronal space is backfilled using melted GP. The implementation of CVC technique has demonstrated an improved coronal adaptation of GP with canal walls. The stated technique seems beneficial; especially in the obturation of severely curved canals or root canals with a final preparation shape of variable taper.